Storytelling Using Picture Books Reduces Anxiety in Hospitalized Preschool Children - Aprilia Sekar Puspita Sari; Nur Eni Lestari; Hari Ghanesia Istiani (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2021)
Introduction: Anxiety is still one of the problems often experienced by preschool-aged children who are hospitalized. One effort that can be done by nurses is to tell stories used a picture book. Objective: This study was to determine the effect of storytelling using picture books on the level of anxiety in preschool-aged children undergoing hospitalizatized. Methods: The study used a quasi-experimental one-group pre-post test design study. The population of this research was preschool children who experience hospitalization. The sample used a purposive sampling technique of 20 respondents. Anxiety research instrument used a standardized questionnaire from the Zung Self Rating Anxiety Scale. Data analysis used marginal homogeneity. Results: This study described the level of anxiety before the intervention was moderate anxiety by 15 respondents (75%) and the level of anxiety after the intervention showed no anxiety as many as 19 respondents (95%). Bivariate analysis showed that the value of p = 0,000. Conclusion: There was an effect of storytelling using picture books on the level of anxiety in pre-school-aged children who have been hospitalized. This can be a recommendation for storytelling using picture books as an alternative to distraction and atraumatic care in reducing anxiety in preschoolers.